Effective regulation of the micro-structure of thick P3HT:PC71BM film by the incorporation of ethyl benzenecarboxylate in toluene solution. Issue 59 (28th June 2015) - Shen, Wenfei; Xiao, Manjun; Tang, Jianguo; Wang, Xinzhi; Chen, Weichao; Yang, Renqiang; Bao, Xichang; Wang, Yao; Jiao, Jiqing; Huang, Linjun; Liu, Jixian; Wang, Wei; et al.
<x xml:space="preserve">Abstract</x> In this work, ethyl benzenecarboxylate (EB) was creatively selected as the additive in a blend of poly(3-hexylthiophene)/phenyl-C71-butyric acid methyl ester (P3HT/PC71BM) in non-halogenated solvent toluene (TL).